Observational study to assess pregnant women’s knowledge and behaviour related to toxoplasmosis in Essaouira province, Morocco - Nadia Ouzennou; Samia Boussaa; Safa Ben Alla; Ali Boumezzough (Asian Pacific Journal of Tropical Medicine, 2019)
Objective: To assess knowledge and behaviour related to toxoplasmosis which remains a neglected disease in Morocco. Methods: Observational investigations were conducted among 600 pregnant women from Essaouira Province. The interview items covered respondents’ knowledge of the disease, its preventive practices and risk behaviours. Results: A total of 22/600 women had already carried out the anti-toxoplasmosis test, while, 96% have never done any screening of anti- Toxoplasma antibodies. Only 16/600 women have good information about the disease, its mode of transmission and its complications in both the fetus and his mother. Although most women adopt a healthy diet, the consumption of raw or undercooked meat is far to be considered as a risk factor, along with other potential factors that may foster the acquisition of the disease, such as possessing a domestic cat, educational status and knowledge of the disease. However, in this study, contact with soil was revealed the most important risk factor (P = 0.045), followed by the hygiene conditions after handling raw meat (P = 0.048). Conclusion: The underestimation of the Toxoplasma gondii sero-prevalence in Essaouira Province can be explained by the absence of toxoplasmosis serology in health institutions, as well as the gap of knowledge about the disease by local population.